AMPK activation is involved in hypoglycemic and hypolipidemic activities of mogroside-rich extract from Siraitia grosvenorii (Swingle) fruits on high-fat diet/streptozotocin-induced diabetic mice. Issue 1 (5th December 2018) - Liu, Hesheng; Qi, Xiangyang; Yu, Keke; Lu, Anjie; Lin, Kaifeng; Zhu, Jiajing; Zhang, Min; Sun, Zhida
Abstract : AMPK is involved in hypoglycemic and hypolipidemic activities of mogrosides from Siraitia grosvenorii (Swingle) fruits on diabetic mice. Abstract : Previous studies suggested the anti-diabetic effect of mogrosides in type 1 diabetes. To evaluate the potential effect of mogrosides in type 2 diabetes, we herein investigated the hypoglycemic and hypolipidemic effects and the underlying mechanism of mogroside-rich extract (MGE) using a high-fat diet in combination with streptozotocin (STZ)-induced diabetic model. MGE feeding for 5 weeks did not result in any obvious impact on the body weight and energy intake, but caused a moderate decrease of organ index in diabetic mice. MGE-supplemented diabetic mice showed a notable reduction of fasting blood glucose (FBG), glycated serum protein (GSP), serum insulin, homeostasis model assessment-insulin resistance (HOMA-IR), and serum atherogenic lipid profiles in a dose-dependent manner, whereas significant increases in the anti-atherogenic lipid profile, insulin sensitivity, glucose and insulin tolerance capacity with high dose (300 mg kg −1 ) MGE were observed ( P < 0.01). Besides, hepatocyte polymorphism, lipid accumulation and steatosis were ameliorated and restored to near normal at the high dose. Furthermore, hepatic 5′AMP-activated protein kinase (AMPK) signaling was dose-dependently activated. Accordingly, the mRNA levels of hepatic gluconeogenic and lipogenic genes were downregulated and fat oxidation-associated genes were upregulated. These findings suggest that the hypoglycemic and hypolipidemic activities of MGE are probably attributed to the attenuation of insulin resistance and activation of hepatic AMPK signaling.